Art therapy facilities as a supportive environment for teen mental health recovery - Farida, Ariesa; Lestari, Indah Puji; Haristianti, Vika; Rangga, Firmansyah; Liritantri, Widyanesti (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
The prevalence of mental health issues among adolescents in Indonesia has significantly increased; however, this rise has not been accompanied by adequate recovery facilities, particularly for this vulnerable age group. Existing mental health recovery facilities predominantly emphasize conventional psychotherapy methods. In contrast, art therapy provides a more engaging and interactive approach by utilizing art as a medium to facilitate the recovery process. Therefore, this study aims to identify the essential facilities required in an art therapy center, particularly in supporting the recovery of mental health disorders among adolescents in Indonesia. The research approach was conducted using an inductive qualitative method, including observation and field surveys at established art therapy facilities. This method, is analyzes data, essentially involving producing an overall summary of the content of the data set. The findings indicate that art therapy is a deeply personal experience for each individual, as it involves expressing emotions. Because of this, the approach should be personalized to each person's unique needs and supported with a variety of art media and appropriate facilities to support a meaningful and effective creative process. Due to the complexity of various methods that can be used in art therapy, further research is needed to explore the relationship between art therapy methods and the design of specialized art therapy spaces.